Antimicrobial and Biofilm-Preventing Activity of l-Borneol Possessing 2(5H)-Furanone Derivative F131 against S. aureus—C. albicans Mixed Cultures - Rand Sulaiman; Elena Trizna; Alena Kolesnikova; Alsu Khabibrakhmanova; Almira Kurbangalieva; Mikhail Bogachev; Airat Kayumov (Pathogens, 2022)
Candida albicans and Staphylococcus aureus are human pathogens that are able to form mixed biofilms on the surface of mucous membranes, implants and catheters. In biofilms, these pathogens have increased resistance to antimicrobials, leading to extreme difficulties in the treatment of mixed infections. The growing frequency of mixed infections caused by S. aureus and C. albicans requires either the development of new antimicrobials or the proposal of alternative approaches to increase the efficiency of conventional ones. Here, we show the antimicrobial, biofilm-preventing and biofilm-eradicating activity of 2(5H)-furanone derivative F131, containing an l-borneol fragment against S. aureus–C. albicans mixed biofilms. Furanone F131 is also capable of inhibiting the formation of monospecies and mixed biofilms by S. aureus and C. albicans. The minimal biofilm-prevention concentration (MBPC) of this compound was 8–16 μg/mL for S. aureus and C. albicans mono- and two-species biofilms. While the compound demonstrates slightly lower activity compared to conventional antimicrobials (gentamicin, amikacin, fluconazole, terbinafine and benzalkonium chloride), F131 also increases the antimicrobial activity of fluconazole–gentamicin and benzalkonium chloride against mixed biofilms of S. aureus–C. albicans, thus reducing MBPC of fluconazole–gentamicin by 4–16 times and benzalkonium chloride twofold. F131 does not affect the transcription of the MDR1, CDR1 and CDR2 genes, thus suggesting a low risk of micromycete resistance to this compound. Altogether, combined use of antibiotics with a F131 could be a promising option to reduce the concentration of fluconazole used in antiseptic compositions and reduce the toxic effect of benzalkonium chloride and gentamicin. This makes them an attractive starting point for the development of alternative antimicrobials for the treatment of skin infections caused by S. aureus–C. albicans mixed biofilms.